If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(6 + 3x) = 28 x + (6 * -1 + 3x * -1) = 28 x + (-6 + -3x) = 28 Reorder the terms: -6 + x + -3x = 28 Combine like terms: x + -3x = -2x -6 + -2x = 28 Solving -6 + -2x = 28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2x = 28 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 28 + 6 -2x = 28 + 6 Combine like terms: 28 + 6 = 34 -2x = 34 Divide each side by '-2'. x = -17 Simplifying x = -17
| 2/3x11/2 | | X^2-16x+y^2=36 | | Y=8x(tanx) | | 9z-14z=207 | | Y=8x(tanc) | | 6+6-6= | | 10+p=6 | | F(x)=15 | | 101-9y=29 | | 7-4x=4+3x | | Y-60=-17//2(x-20) | | 42-2x=5 | | -2x-2=2x+14 | | 13-6x=7-8x | | 122/75 | | We+14=8(q+7) | | -31+a=-6 | | 5x^2-14+49=0 | | 3(x-1)-4(x-1)=36x+24 | | -8(x/2-y/4)= | | x+squrt(4x)-5=0 | | ln(4x-3)+ln(x+1)= | | -2(4a+3b)= | | -11+y=-31 | | 5+6log^2x=14 | | -1=3(3x-2) | | (3x^2y)(5x^2y^2-6xy+2)= | | (2x+20)(5x-20)=1200 | | 100-2x=50 | | -4/7x=32 | | (2x+20)(5x-20)= | | -6=6(w-9) |